Shift In Menarche Age Among Generations X, Y, Z, And Alpha In Jember District 2023: Pergeseran Menarch Antar Generasi X, Y, Z, Dan Alpha Di Kabupaten Jember 2023 - Lulut Sasmito; Luthfi Eka; Kiswati; Jenie Palupi (Jurnal Kesehatan dr. Soebandi, 2023)
Introduction: Menarche is defined as the first menstrual period in a female adolescent.This study aims to evaluate the shift in the age of menarche among four generations: Generation X, Y, Z, and Alpha in Jember Regency. Methods: The research design used a quantitative approach with survey methode. This study used nonprobability sampling, consecutive sampling which divided the responden on 274 female adolescent of different numbers in each generation studied. Data were collected through questionnaires and analyzed using One way Anova. Results: The results showed that the age of menarche shifted among the generations studied. Generation Alpha had an earlier age of menarche than the previous generation. Additionally, there was a significant difference in the age of menarche between Generation X and Y, and Generation Y and Z, with Generation X experiencing a delay in the age of menarche compared to Generation Y, and Generation Z experiencing an acceleration in the age of menarche compared to Generation Y. Conclusion: This study concludes that a shift in the age of menarche occurs among Generation X, Y, Z, and Alpha in Jember Regency. This indicates a change in environmental and lifestyle factors that affect the age of menarche. Discussion: The results of this study are expected to be a reference for further research on factors influencing the shift in the age of menarche and health implications related to this shift. Keywords: Menarche, shift, Generation X, Y, Z, and Alpha.